Genetic diversity of wild barley (Hordeum spontaneum K. Koch) in the context of resistance to toxic aluminum ions - O. V. Yakovleva (Труды по прикладной ботанике, генетике и селекции)
Background. The problem of resistance to aluminum toxicity of soils is very relevant for the cultivated type of barley. The area of acidic soils in Russia is about forty percent of the total area of arable land, so the toxicity of aluminum is one of the main factors that reduce the yield of barley. The study of wild relatives of the main crops, including barley, is of considerable interest for the development of stress-resistant cultivars. Wild barley Hordeum spontaneum K. Koch has biological characteristics similar to the cultivated H. vulgare L., grows in various ecogeographic zones, and is well adapted to local soil and climate conditions. All this makes it possible to use it as a new donor of source material for breeding high-yielding cultivars adapted to certain environmental conditions. The objective of this work was to search for H. spontaneum genotypes highly resistant to ionic (Al3+) toxicity.Materials and methods. One hundred accessions of H. spontaneum from the collection of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) were examined. The resistance of barley accessions to toxic aluminum ions was studied at the early stages of plant development by the root test method (185 mcМ Al3+, pH 4.0) with the calculation of root and sprout length indices.Results and conclusions. The studied fragment of the wild barley collection demonstrated broad genetic diversity in terms of resistance to phytotoxic aluminum ions. Laboratory assessment allowed us to identify barley genotypes differing in the reaction of their roots and sprouts at the early phases of ontogenesis. The identified genotypes with a high level of resistance to ion stress can be used as a valuable source of genetic material to improve existing cultivars and develop new ones by introgression of foreign resistance genes.